2010
DOI: 10.1007/s10558-010-9100-5
|View full text |Cite
|
Sign up to set email alerts
|

Design, Fabrication and Analysis of Silicon Hollow Microneedles for Transdermal Drug Delivery System for Treatment of Hemodynamic Dysfunctions

Abstract: In this paper, we present design, fabrication and coupled multifield analysis of hollow out-of-plane silicon microneedles with piezoelectrically actuated microfluidic device for transdermal drug delivery (TDD) system for treatment of cardiovascular or hemodynamic disorders such as hypertension. The mask layout design and fabrication process of silicon microneedles and reservoir involving deep reactive ion etching (DRIE) is first presented. This is followed by actual fabrication of silicon hollow microneedles b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 51 publications
1
51
0
1
Order By: Relevance
“…Reproduced with permission from Elsevier. [8] [26] Polylactic acid (PLA) [27] Polyvinyl acetate (PVA) [18] Thermoplastic starch [28] Stainless steel [29] Polyglycolic acid (PGA) [27] Alginic acid [18] Carboxymethylcellulose [30] Titanium 19 Polylactide-co-glycolic acid (PLGA) [27] Gantrez AN-139, a copolymer of methylvinylether and maleic anhydride (PMVE/MA) [18] Amylopectin [30] Mesoporous silicon [31] Polycarbonate [16] Carbopol 971 P-NF 18 Dextran, galactose, chondroitin sulfate [32] Polyvinylpyrrolidone (PVP) [33] Polyetherimide [34] Maltose [35] Microneedles: an emerging drug delivery Shital H. Bariya et al…”
Section: Materials Used To Constitute Microneedlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Reproduced with permission from Elsevier. [8] [26] Polylactic acid (PLA) [27] Polyvinyl acetate (PVA) [18] Thermoplastic starch [28] Stainless steel [29] Polyglycolic acid (PGA) [27] Alginic acid [18] Carboxymethylcellulose [30] Titanium 19 Polylactide-co-glycolic acid (PLGA) [27] Gantrez AN-139, a copolymer of methylvinylether and maleic anhydride (PMVE/MA) [18] Amylopectin [30] Mesoporous silicon [31] Polycarbonate [16] Carbopol 971 P-NF 18 Dextran, galactose, chondroitin sulfate [32] Polyvinylpyrrolidone (PVP) [33] Polyetherimide [34] Maltose [35] Microneedles: an emerging drug delivery Shital H. Bariya et al…”
Section: Materials Used To Constitute Microneedlesmentioning
confidence: 99%
“…[81,82] Ashraf et al designed a microfluidic drug delivery device with an electronic module, sensor for blood pressure and flow, and drug delivery device as its main components. [26] The system automatically injected the desired drug dose through microneedles at a controlled rate on sensing an increase in blood pressure.…”
Section: Drugsmentioning
confidence: 99%
“…Hollow MNs usually require very precise and high cost manufacturing technology, which prevent them from large scale production [26]. In this approach, large scale reproduction with low costs is pursued sometimes based on self-assembly and molding of soft materials.…”
Section: Problems Of Non-hydrogel Mnsmentioning
confidence: 99%
“…High aspect ratio microneedles have been developed for blood sampling [13]. Fabrication of silicon microneedles and simulation of microfluidic device with piezoelectric actuation mechanism have been reported for transdermal drug delivery [14]. Hollow microneedles have been developed by using SU-8 fabrication technique for transdermal drug delivery and blood extraction [15].…”
Section: Introductionmentioning
confidence: 99%
“…Donnelly et al [18] reported polymeric microneedles for intradermal delivery. Waseem et al [14] developed silicon microneeldes and conducted structural analysis by applying force of 8.5 N on microneedle. Stress of 6.78 GPa was observed on microneedle.…”
Section: Introductionmentioning
confidence: 99%